Algunas cuestiones sobre la reducción nominal del capital social por pérdidas en la sociedad anónima - Baena Baena, Pedro Jesús (Homenaje en memoria de Joaquín Lanzas y de Luis Selva, 1998)
Accepted: 2018-10-25T10:10:34Z

Intellectual Property Rights and Competition: A Framework for the Analysis of Economic and Legal Issues - Gallini, Nancy; Trebilcock, Michael (Competition Policy and Intellectual Property Rights in the Knowledge-Based Economy, 1998)
This is the version of record of a chapter authored by Nancy Gallini and Michael Trebilcock, and published by the University of Calgary Press.
Accepted: 2023-08-03T16:16:10Z
Keywords: Competition Policy; Economic Literature Review; Intellectual property